Ultrasound guided pulmonary artery catheter insertion: An alternative to fluoroscopic guidance. (2022) - Josan, Enambir; Pastis, Nicholas; Shaman, Ziad
Abstract: Pulmonary artery catheters (PACs) can provide extremely valuable objective data in select patients. They are usually advanced by floatation of balloon tip along the normal blood flow and their placement is confirmed under pressure waveform guidance. Imaging such as fluoroscopy is often employed in low flow states and in cardiac catheterization suite to reduce the failure rate and time to wedge; but is not readily available at bedside. In critically ill patient, bedside insertion is feasible but can be complicated by repeated attempts to float the balloon tip through various cardiac chambers. Point of care ultrasound can be used to visualize the balloon tip of PAC inside the cardiac chambers alongside the confirmatory pressure waveform changes.